Validitas metode rinohigrometri sebagai indikator sumbatan hidung - Rachmawati Djalal; Abdul Qadar Punagi; Andi Baso Sulaiman; Fadjar Perkasa (PERHATI-KL, 2011)
Background: The narrowing of nasal cavity due to nasal mucosa changes or other factors may leadsto nasal obstruction. Symptoms of nasal obstruction can be classified from mild to severe and in somecases total obstruction may occur. Purpose: The objective of the research was to determine the validity of rhinohygrometric method as nasal obstruction indicator. The complaint of nasal obstruction depicted theexistence of abnormalities either anatomically, physiologically or pathologically. The evaluation of thenasal obstruction was based on anamnesis, physical examination and also supporting examination forthe measurement of the nasal patency. Method: An analytic study had been carried out on the diagnostic test for determining sensitivity and specificity values of rhinohygrometeric method as nasal obstruction indicator compared with peak nasal inspiratory flow (PNIF) as the basic standard on subjects who hadnasal obstruction and subjects who did not have nasal obstruction. Results: In the research, the valuesof cutting off point rhinohygrometeric method are 3 cm and 4 cm on the length and width, while thevalue of basic standard of PNIF cutting off point is 80 liter/minute. Sensitivity and specificity methodof rhinohygrometeric on the length were 87.8% and 100% while on the width were 95.1% and 89.8%.Conclusion: Rhinohigrometeric method has validity as indicator of nasal obstruction. Keywords: rhinohygrometeric method, nasal obstruction, cutting off point, sensitivity and specificity Abstrak : Latar belakang: Setiap penyempitan rongga hidung baik akibat proses perubahan pada mukosahidung ataupun penyebab yang lain akan mengakibatkan timbulnya gejala sumbatan hidung. Gejalasumbatan hidung dapat bersifat ringan sampai berat bahkan dapat terjadi sumbatan total. Tujuan: Untukmenentukan validitas metode rinohigrometri sebagai indikator sumbatan hidung. Metode: Penelitian inimenggunakan studi analitik terhadap uji diagnostik untuk menentukan nilai sensitivitas dan spesifisitasmetode rinohigrometri sebagai indikator sumbatan hidung dibandingkan dengan peak nasal inspiratoryflow (PNIF) sebagai standar baku pada subjek yang mengalami sumbatan hidung dan subjek yang tidakmengalami sumbatan hidung. Hasil: Penelitian menunjukkan bahwa telah ditetapkan nilai titik potongmetode rinohigrometri adalah 3 cm dan 4 cm pada sisi panjang dan lebar, sedangkan nilai titik potongstandar baku PNIF adalah 80 liter/menit. Sensitivitas dan spesifisitas metode rinohigrometri padasisi panjang adalah 87,8% dan 100%, sedangkan pada sisi lebar adalah 95,1% dan 89,8%. Kesimpulan:Metode rinohigrometri memiliki validitas sebagai indikator sumbatan hidung. Kata kunci: metode rinohigrometri, sumbatan hidung, titik potong, sensitivitas, spesifisitas